2009
DOI: 10.1111/j.1743-6109.2009.01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Arousal by Higher- and Lower-Ranking Partner: Manifestation of a Mating Strategy?

Abstract: Background High hierarchical status is associated with increased reproduction success in mammals. However the subordinate males are not totally eliminated from reproduction due to mate choice and alternative male strategies. Thus; the sexual arousal by higher-ranking or lower-ranking partner in humans may represent a proximate mechanism for realizing a reproductive strategy. Aim To evaluate possible connection between mating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Furthermore, we found that men with high arousal gave higher attractiveness ratings to female faces. Because we used the resting‐state EEG before the participants viewed attractive faces, the enhancement of facial attractiveness may be associated with the general arousal state rather than sexual arousal specifically (Jozifkova & Konvicka, 2009 ), thus supporting the idea that general arousal improves judgment of attractiveness in men.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, we found that men with high arousal gave higher attractiveness ratings to female faces. Because we used the resting‐state EEG before the participants viewed attractive faces, the enhancement of facial attractiveness may be associated with the general arousal state rather than sexual arousal specifically (Jozifkova & Konvicka, 2009 ), thus supporting the idea that general arousal improves judgment of attractiveness in men.…”
Section: Discussionmentioning
confidence: 92%
“…Definitely, the fundamentals of conflict and coexistence do exist in reproduction, and therefore, the benefits and costs must exist as well. Appreciating the balance between the benefits and costs of reproduction is crucial for our understanding of genital evolution as a whole [42,43].…”
Section: Discussionmentioning
confidence: 99%